Bilateral Reduction Mammoplasty with Nipple-areola Complex Graft in Ten-Year-Old Girl with Juvenile Gigantomastia: A Case Report - Khadija Ali; Manar Husain; Amal Alrayes; Hussain Alsaffar (Oman Medical Journal)
Gigantomastia is a rare benign disorder characterized by excessive breast enlargement. Although a standard definition has yet to be established, it is generally known as an excess of approximately 1.5 kg tissue per breast that requires reduction. We report a case of a 10-year-old girl who presented with enlarged breasts. The hormonal assay was normal. Breast ultrasound revealed increased fibroglandular breast tissue with an area of interstitial fluid, prominent vascularity, and dilated veins. There was no evidence of focal masses or collections, ductal ectasia, or axillary lymphadenopathy. Magnetic resonance imaging revealed extremely dense breasts with more than 75% fibroglandular tissue, consistent with juvenile breast hypertrophy. Bilateral reduction mammoplasty with nipple-areola complex graft was performed. The histopathological report confirmed benign gigantomastia.